UM ESTUDO DE VOCÁBULOS RECORRENTES E SUAS TRADUÇÕES EM DUAS OBRAS DE CLARICE LISPECTOR - Lima, Thereza Cristina de Souza (2010)
Having identified “life/death” as a couple of Lispector’s preferential key-words in our corpora, we analysed aspects of normalization in relation to them. For theoretical support on corpusbased translation research, we used Baker’s (1993, 1996, ), Berber Sardinha’s (2004) and Scott’s (1998) proposals; for the literary approach, we followed Nunes (1995).